ANDROID-BASED MOBILE LEARNING MEDIA IN TEACHING READING OF REPORT TEXTS - Muhfiyanti Muhfiyanti; Dodi Mulyadi; Siti Aimah (Getsempena English Education Journal, 2021)
Mobile phones can be well integrated into English Instruction as the creativity and innovation of teaching media increase students’ interest and motivation. This research aims to reveal the validity, effectiveness, and practicality of utilizing Android-based Mobile Learning Media for teaching reading report texts. The present research employed the research and development design. The research instruments were questionnaires, tests, and learning media in Application Package Files (APK). The collected data were analyzed by employing descriptive statistics and inferential statistics with a t-test. This research’s subject was an experimental class and a control class in Senior High School of Muhammadiyah 2 of Purbalingga. The expert validation results were categorized into relevant and feasible learning media to teach report texts. The pre-test and post-test mean scores in the experimental class showed a highly significant difference because the class outperformed the control class. It means that Android-based MLM was effective for enhancing students’ reading comprehension of report texts. Meanwhile, the result of students’ perception obtained a good category. The data reveal that 70.4% of the students agreed to use Android-based MLM in the learning process. This research concludes that the final product meets the criteria of teaching media evaluation.